SETTLEMENT OF DISPUTES OVER THE INHERITANCE PROPERTY DISTRIBUTION IN THE COMMUNITY OF JUWONO VILLAGE, NGANJUK - Poespasari, Ellyne Dwi; Helmi, Hanum Rahmaniar; Soelistyowati, Soelistyowati; Sumedi, Muhammad; Erlangga, Afga Samudera (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Inheritance disputes in the community of Juwono Village, Kertosono, Nganjuk, East Java, occur because there are several family parties who perceive that the distribution of inheritance has not been fair or not getting any part of the inheritance divided by the inheritor. This disagreement can lead to disputes among family members. This research aims to find out the fair inheritance distribution in Juwono Village community and its settlement. This research is a socio-legal research with an analytical descriptive approach. The results of this research indicated that inheritance distribution disputes that often occur in Juwono Village are disputes related to widows, widowers, biological children, adopted children, extra-marital children, and stepchildren who do not get the share of inheritance that has been determined by inheritance law. If the inheritance distribution dispute cannot be resolved through deliberation within the family or with the help of village officials, then the parties can file a lawsuit to the court.